Veterinarians as a Risk Group for Zoonoses: Exposure, Knowledge and Protective Practices in Finland - Paula M. Kinnunen; Alisa Matomäki; Marie Verkola; Annamari Heikinheimo; Olli Vapalahti; Hannimari Kallio-kokko; Anna-Maija Virtala; Pikka Jokelainen (Elsevier, 2022)
Background: Veterinarians may encounter a variety of zoonotic pathogens in their work. Methods: We conducted two cross-sectional questionnaire studies among veterinarians in Finland. Participants were recruited during two Annual Veterinary Congresses. In 2009, 306 veterinarians participated in an extensive questionnaire study, and in 2016, 262 veterinarians participated in a more focused study that included two same questions. Results: In 2009, the majority (90.9%) of the participating veterinarians reported having been occupationally exposed to zoonotic pathogens. Zoonotic infections (15.0%), needle stick incidents (78.8%), bites (85.0%), as well as infected skin lesions (24.2%) were reported. In 2009, 8.2% of the participants fully agreed with the statement "I have good knowledge of zoonoses and their prevention"; in 2016, the proportion was 10.3%. The reported use of protective practices and personal protective equipment in connection with specific veterinary procedures indicated that there was room for improvement, particularly in protection from pathogens that are transmissible via inhalation and mucous membranes. Conclusion: The results confirm that veterinarians are commonly occupationally exposed to zoonotic pathogens. Education should aim to improve and maintain the knowledge of zoonoses and their prevention. Use of protective practices should be advocated.